Migration route and wintering area of Tundra Swans Cygnus columbianus nesting in the Kobuk-Selawik Lowlands, North-West Alaska - Moermond, Jack E; Spindler, Michael A (Wildfowl, 1997)
Tundra Swans were marked with colour-coded neck collars (n=115) on their nesting grounds in the Kobuk-Selawik lowlands of north-west Alaska during late summer 1984-1989. Resightings of 62 individual swans were obtained in Alaska, four Canadian provinces and eight states in western United States (US) during 1984-96. Observations of Kobuk-Selawik Tundra Swans occurred along a narrow route through Alaska and the Yukon Territory, and along two trans-Rocky Mountain routes, before narrowing to their wintering grounds in north-central California, primarily the Sacramento Valley. Repeated observations of several marked swans indicated traditional use of the same migration stop-over sites and wintering areas during successive years. Occasionally, Tundra Swans marked in north-west Alaska mixed with swans of the Eastern population during migration and in winter.